Glass Ionomer Cements Based in TiO2 by Sol-gel Method - Ilipronti, Thiago; Clare, Carolina Kleinibing; Berndt, Graciele; de Campos, Elvio Antônio; Fernandes, Maria Helena Vaz; de Campos, Silvia Denofre (Orbital: The Electronic Journal of Chemistry, 2019)
Glass ionomer cements are used in dentistry for applications such as luting cements and as restoratives materials, due to their ability to chemically bond to the tooth. The glasses used in the cements are based on calcium aluminum silicates and calcium fluoride. This study aimed at preparing a glass systems containing titanium oxide to be used in glass ionomer cements. Powders with the composition 47SiO2-13CaO-29Na2O-7P2O5-4TiO2 were synthesized by the sol-gel method, one prepared with TiO2 powder (A1) and the other with titanium tetraisopropoxide (A2). The obtained powders exhibited a specific surface area of 83.63 m2g-1 and 15.79 m2g-1 and pore diameter of 42.07 Å and 90 Å for A1 and A2, respectively. The XRD results indicated that the material is partially crystalline with weak diffraction peaks related to titanium oxide (anatase). The FTIR and Raman spectroscopy analyses showed that SiO4 tetrahedra are found in the same coordination both in the synthesized glasses network and in the commercial glass ionomer cements Vidrion C® Cementation and Maxion®R Restorative, used for comparative purposes. The introduction of Ti4+ ions in the powders developed in this work provided properties and the structural characteristics indicating their potential for applications as ionomer cements.DOI: http://dx.doi.org/10.17807/orbital.v11i1.1176